Critical perspectives on teaching, learning, and society - Miller, Paul Chamness; Reagan, Timothy; Schwieter, John W.; McGivern, Cuhullan Tsuyoshi; Ho, Jason Man-Bo (Readings in language studies., 2022)
Founded in 2002, the International Society for Language Studies is a worldwide organization of volunteers, scholars, and practitioners committed to critical, interdisciplinary, and emergent approaches to language studies. Its eighth volume of the Readings in Language Studies series, Critical Perspectives on Teaching, Learning, and Society, presents international perspectives on issues of language related to a variety of themes.